Question
d) \( -9+(4-10)-5(-3-7)+19 \)
Ask by Howell Frazier. in Colombia
Feb 04,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
El resultado es 54.
Solution
Para resolver la expresión:
\[ -9 + (4 - 10) - 5(-3 - 7) + 19 \]
**Paso 1: Resolver los paréntesis**
1. \(4 - 10 = -6\)
2. \(-3 - 7 = -10\)
Sustituyendo estos resultados en la expresión:
\[ -9 + (-6) - 5(-10) + 19 \]
**Paso 2: Realizar la multiplicación**
\[ -5 \times (-10) = 50 \]
Ahora la expresión queda:
\[ -9 - 6 + 50 + 19 \]
**Paso 3: Sumar los términos**
1. \(-9 - 6 = -15\)
2. \(-15 + 50 = 35\)
3. \(35 + 19 = 54\)
**Resultado final:**
\[ 54 \]
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Mind Expander
Let’s simplify this expression step by step! First, we deal with the parentheses: \( -9 + (4 - 10) - 5(-3 - 7) + 19 \) simplifies to \( -9 - 6 - 5(-10) + 19 \). Now we have \( -9 - 6 + 50 + 19 \) since \( -5 \times -10 = 50 \). Next, combine the numbers: \( -9 - 6 = -15 \), and \( -15 + 50 = 35 \), then finally \( 35 + 19 = 54 \). So, the answer is \( 54 \)!